71.6k views
0 votes
In each of the following


find \: (dy)/(dx)\:

a)\: \: y = \sin ^ - 1 √(x) + ln( √(x) )


b) {e}^(y) = {2}^(x) log(x) - {e}^(2x)


User Paul Erdos
by
4.6k points

1 Answer

2 votes

(a) Recall that


(\mathrm d[\sin^(-1)x])/(\mathrm dx)=\frac1{√(1-x^2)}


(\mathrm d[\ln x])/(\mathrm dx)=\frac1x


(\mathrm d[\sqrt x])/(\mathrm dx)=\frac1{2\sqrt x}

Then by the chain rule,


y=\sin^(-1)(\sqrt x)+\ln(\sqrt x)


\implies(\mathrm dy)/(\mathrm dx)=(\mathrm d[\sin^(-1)(\sqrt x)+\ln(\sqrt x)])/(\mathrm dx)


=\frac1{√(1-(\sqrt x)^2)}(\mathrm d[\sqrt x])/(\mathrm dx)+\frac1{\sqrt x}(\mathrm d[\sqrt x])/(\mathrm dx)


=\frac1{2\sqrt x√(1-x)}+\frac1{2(\sqrt x)^2}


=\frac1{2√(x-x^2)}+\frac1{2x}


=\boxed{(x+√(x-x^2))/(2x√(x-x^2))}

(b) I'll assume
\log x refers to the logarithm of base
e. Recall that


(\mathrm d[e^x])/(\mathrm dx)=e^x


2^x=e^(\log2\,x)\implies(\mathrm d[2^x])/(\mathrm dx)=e^(\log2\,x)(\mathrm d[\log2\,x])/(\mathrm dx)=\log2\cdot2^x

Then using the chain rule and implicit differentiation, we get


e^y=2^x\log x-e^(2x)


\implies e^y(\mathrm dy)/(\mathrm dx)=(\mathrm d[2^x])/(\mathrm dx)\log x+2^x(\mathrm d[\log x])/(\mathrm dx)-e^(2x)(\mathrm d[2x])/(\mathrm dx)


e^y(\mathrm dy)/(\mathrm dx)=\log2\cdot2^x\log x+\frac{2^x}x-2e^(2x)


(\mathrm dy)/(\mathrm dx)=\frac{\log2\cdot2^x\log x+\frac{2^x}x-2e^(2x)}{e^y}


(\mathrm dy)/(\mathrm dx)=\frac{\log2\cdot2^x\log x+\frac{2^x}x-2e^(2x)}{2^x\log x-e^(2x)}


(\mathrm dy)/(\mathrm dx)=\boxed{(\log2\cdot2^xx\log x+2^x-2xe^(2x))/(x(2^x\log x-e^(2x)))}

If instead
\log x=\log_(10)x denotes the base 10 logarithm, you need only make the following adjustment:


\log x=(\ln x)/(\ln 10)\implies(\mathrm d[\log_(10)x])/(\mathrm dx)=\frac1{\ln10\,x}

where
\ln x is logarithm of base
e.

User Sana Mumtaz
by
4.5k points